2005
DOI: 10.1123/jsr.14.2.150
|View full text |Cite
|
Sign up to set email alerts
|

Self-Efficacy, Imagery Use, and Adherence to Rehabilitation by Injured Athletes

Abstract: Objective:To evaluate the factorial validity of the Athletic Injury Self-Efficacy Questionnaire (AISEQ) and the predictive relationships among self-efficacy, imagery use, and rehabilitation adherence.Design and Setting:Survey administered in an outpatient physiotherapy clinic.Participants:270 injured athletes.Main Outcome Measures:AISEQ, Athletic Injury Imagery Questionnaire, and an adherence measure.Results:A confirmatory factor analysis of the AISEQ revealed a 2-factor model. Athletes were higher in task eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
64
3

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(73 citation statements)
references
References 35 publications
4
64
3
Order By: Relevance
“…Additional research further supports these findings. [8][9][10]28,[31][32][33][34] Such results are not surprising because athletes, especially students at the collegiate level, typically experience several stressors (eg, increased academic and athletic demands, public scrutiny, and competitive pressures) for which they may not have the necessary coping skills, and encountering an injury only adds to the existing stressors. 35 Moreover, these increased stress levels are likely to have a negative effect on an athlete's overall well being and self-worth, subsequently leading to increased levels of anxiety.…”
Section: Discussionmentioning
confidence: 99%
“…Additional research further supports these findings. [8][9][10]28,[31][32][33][34] Such results are not surprising because athletes, especially students at the collegiate level, typically experience several stressors (eg, increased academic and athletic demands, public scrutiny, and competitive pressures) for which they may not have the necessary coping skills, and encountering an injury only adds to the existing stressors. 35 Moreover, these increased stress levels are likely to have a negative effect on an athlete's overall well being and self-worth, subsequently leading to increased levels of anxiety.…”
Section: Discussionmentioning
confidence: 99%
“…[9][10][11] Of these factors, goal setting has been suggested to enhance patient motivation and treatment adherence by promoting higher levels of self-efficacy and treatment efficacy. 9,12,13 Likewise, a number of studies have reported that a strong belief in treatment efficacy is related to patient adherence to injury rehabilitation programmes. 9,12,13 There is also evidence indicating that belief in the efficacy of treatment is a powerful predictor of adherence.…”
Section: Introductionmentioning
confidence: 99%
“…9,12,13 Likewise, a number of studies have reported that a strong belief in treatment efficacy is related to patient adherence to injury rehabilitation programmes. 9,12,13 There is also evidence indicating that belief in the efficacy of treatment is a powerful predictor of adherence. 12,14 Hence, the identification of techniques that enhance a patient's belief in the efficacy of treatment may provide a basis upon which to design interventions that increase adherence and enhance the rehabilitation process.…”
Section: Introductionmentioning
confidence: 99%
“…Successful athletic injury rehabilitation is enhanced through proper adherence to a prescribed rehabilitation program (Bassett, 2006;Brewer et al, 2000). Further, previous research has shown that higher levels of self-efficacy are significantly associated with better adherence to such a program (Brewer et al, 2003;Milne, Hall, & Forwell, 2005;Woodgate, Brawley, & Weston, 2005). Therefore, self-efficacy may play an important role in an injured athlete's motivation to recover, subsequent adherence to a prescribed rehabilitation program, and treatment outcome.…”
Section: Imagery and Self-efficacy In The Injury Contextmentioning
confidence: 99%
“…A variable related to self-efficacy in rehabilitation is an injured athlete's imagery use (Milne et al, 2005;Wesch, et al, 2011). Imagery has been described as "an experience that mimics real experience, and involves using a combination of different sensory modalities in the absence of actual perception" (Cumming & Ramsey, 2008, p.5).…”
Section: Imagery and Self-efficacy In The Injury Contextmentioning
confidence: 99%